Discriminative Ability and Predictive Validity of the Timed Up and Go Test in Identifying Older People Who Fall: Systematic Review and Meta‐Analysis. Issue 2 (25th January 2013) - Schoene, Daniel; Wu, Sandy M.‐S.; Mikolaizak, A. Stefanie; Menant, Jasmine C.; Smith, Stuart T.; Delbaere, Kim; Lord, Stephen R.
<x xml:space="preserve">Abstract</x> Objectives To investigate the discriminative ability and diagnostic accuracy of the Timed Up and Go Test (TUG) as a clinical screening instrument for identifying older people at risk of falling. Design Systematic literature review and meta‐analysis. Setting and Participants People aged 60 and older living independently or in institutional settings. Measurements Studies were identified with searches of the PubMed, EMBASE, CINAHL, and Cochrane CENTRAL data bases. Retrospective and prospective cohort studies comparing times to complete any version of the TUG of fallers and non‐fallers were included. Results Fifty‐three studies with 12, 832 participants met the inclusion criteria. The pooled mean difference between fallers and non‐fallers depended on the functional status of the cohort investigated: 0.63 seconds (95% confidence (CI) = 0.14–1.12 seconds) for high‐functioning to 3.59 seconds (95% CI = 2.18–4.99 seconds) for those in institutional settings. The majority of studies did not retain TUG scores in multivariate analysis. Derived cut‐points varied greatly between studies, and with the exception of a few small studies, diagnostic accuracy was poor to moderate. Conclusion The findings suggest that the TUG is not useful for discriminating fallers from non‐fallers in healthy, high‐functioning older people but is of more value in less‐healthy, lower‐functioning older people. Overall, the predictive ability and diagnostic accuracy of the TUG are at best moderate. No cut‐point can be recommended. Quick, multifactorial fall risk screens should be considered to provide additional information for identifying older people at risk of falls.